THE EFFECT OF IMPLEMENTING GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE ON COMPANY FINANCIAL PERFORMANCE - Dwicahyani, Mutia; Nugroho, Hendrato Setiabudi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
The mining sector is an industrial sector characterized by capital and technology-intensive business characteristics, and cannot be renewed. Companies that implement Green Accounting are business entities that prioritize environmental sustainability in their operations and financial management. Companies that are committed to environmental performance not only consider financial aspects, but also pay attention to the ecological impacts of their operational activities. This study aims to evaluate the effect of the implementation of Green Accounting and Environmental Performance on the Financial Performance of Mining Companies in the Coal sub-sector listed on the Indonesia Stock Exchange (IDX). The data used are secondary data from the annual financial reports of companies listed on the IDX for the period 2019-2023. This study covers a population of 8 companies, with a sample of 40 data. The method used is descriptive statistics. The results of the partial t-test show that Green Accounting and Environmental Performance do not affect the Company's Financial Performance individually. However, the F test shows that Green Accounting and Environmental Performance simultaneously affect the Company's Financial Performance.